2005
DOI: 10.1538/expanim.54.107
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Study of Subcapsular Cell Hyperplasia in the Adrenal Glands of IQI/Jic Mice

Abstract: Hyperplastic cells in subcapsular cell hyperplasia (SCH) lesion in adrenal glands

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The adrenal glands, the main peripheral source of glucocorticoids, have a remarkable tissue plasticity that allows their remodeling with age (Bland et al, 2003). SCH, one of the characteristics of adrenal tissue remodeling, is histologically distinct from tumors and dysplasia (Kim et al, 2005;Kovatch et al, 1986;Yoshida et al, 1986). We have now demonstrated that SCH is functionally different as well.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The adrenal glands, the main peripheral source of glucocorticoids, have a remarkable tissue plasticity that allows their remodeling with age (Bland et al, 2003). SCH, one of the characteristics of adrenal tissue remodeling, is histologically distinct from tumors and dysplasia (Kim et al, 2005;Kovatch et al, 1986;Yoshida et al, 1986). We have now demonstrated that SCH is functionally different as well.…”
Section: Discussionmentioning
confidence: 72%
“…The adrenal gland is a highly plastic tissue that remodels with age (Bland et al, 2003). Development of subcapsular cell hyperplasia (SCH), a common histological change distinct from tumors and dysplasia, is known as one of the characteristics of adrenal tissue remodeling in rodents and humans (Aiba and Fujibayashi, 2011;Kim et al, 2005;Kovatch et al, 1986;Yoshida et al, 1986). In this report, we describe the unexpected effects of adrenal SCH on circulating glucocorticoid levels and anxiety-like behaviors.…”
Section: Introductionmentioning
confidence: 91%
“…In addition, lymphocytic infiltration can occur in multiple exocrine and non-exocrine organs, such as pancreas, kidneys, and lungs [104]. As such, this strain has been used for the study of other diseases, such as dermatitis [105], colitis [106] and adrenal cell hyperplasia [107]. Of note, ANA were detected but neither anti-SSA/Ro nor anti-SSB/La autoantibodies were detected from their sera [103].…”
Section: Mouse Modelsmentioning
confidence: 99%
“…The proliferation may occur in a focal or diffuse pattern and it may progress to subcapsular tumor (Taylor 2012; Bernichtein, Peltoketo, and Huhtaniemi 2009). In IQI/Jic female mice, it has been suggested that based on their ultrastructural features (e.g., elongated mitochondria with lamellar cristae and round mitochondria with tubular cristae), hyperplastic cells in subcapsular hyperplasia might be adrenal pluripotent progenitor cells that are located in the zona glomerulosa or in the junction of the zona glomerulosa/fasciculata (Kim et al 2005). In our study, it was the most common proliferative lesion in both sexes, with a much higher incidence in females.…”
Section: Discussionmentioning
confidence: 99%